Vertical profiles of phosphate in the lacustrine and transition zones in the Koto Panjang Reservoir, XIII Koto Kampar Districts, Kampar Regency, Riau Province. - Sistim Wehalo; Asmika H. Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Phosphate is a nutrient that plays as a limiting factor for aquatic organisms and it may affect the aquatic productivity. This research aims to understand the vertical profile of phosphate in the lacustrine and transition zones of the Koto Panjang Reservoir. This research was conducted in September-October 2015. A survey method was applied in this research. Water samplings were conducted 3 times, once/2 weeks. The sampling areas were in the lacustrine and transition zones, two stations in each zone (L1; L2; T1 and T2). Phosphate concentration was analysed based on APHA (2012). Data obtained were then analyzed using a two way ANOVA. Results shown that the surface phosphate concentration in the lacustrine zone was 0.13 mg/L, while that of the transition zone was 0.15 mg/L. Phosphate concentration in the bottom area was slightly higher, it was 0.18 mg/L in the lacustrine and 0.19 mg/L in the transition zone. Result of statistical analysis indicate that there was no difference in the surface’s and bottom’s phosphate concentration in both sampling areas. Based on data obtained, it can be concluded that the Koto Panjang reservoir can be categorized as mesotrophic.Keywords: Koto Panjang reservoir, phosphate, lacustrine and transition